Penggunaan Mobile Payment Pada Mahasiswa Telkom University - Sri Rahayu; Pamungkas Rafli Priyanto (Universitas Sains dan Teknologi Komputer, 2023)
This research aimed to analyze the effect of perceived usefulness, perceived ease of use, perceived trust, and perceived risk on the use of mobile payments by Telkom University students. The use of mobile payments is a method that can be used as an alternative to cash, checks, credit cards, and debit cards and can create new opportunities for payment methods. The population in this study was all Telkom University students. The sampling technique used is the probability sampling technique. The sample used was 282 respondents. Data was obtained through the distribution of questionnaires through Google Forms. The analytical method uses multiple linear regression analysis using SPSS version 26 software. The results show that perceived usefulness, perceived ease of use, perceived trust, and perceived risk have a positive effect on the use of mobile payments. The results of this study are expected to provide an overview for digital payment service providers to improve service quality in using mobile payments so that they can maintain user consistency, increase security so the user trust does not decrease, and pay attention to risks that may occurarticle.